Warmed and humidified insufflation to prevent perioperative hypothermia and improve the quality of recovery in elective laparoscopic colorectal resection patients: a feasibility study for a triple‐blind randomized controlled trial. (23rd November 2021) - Reeves, Nicola; White, Judith; Bird, Samuel; Shinkwin, Michael; Cornish, Julie; Torkington, Jared
Abstract: Aim: The use of standard CO2 for insufflation during laparoscopic colorectal surgery may be associated with cooling and drying of the peritoneal cavity, contributing to perioperative hypothermia. The aim of this work was the assess the feasibility of a study to compare insufflation of warmed, humidified CO2 (WHCO2) (using HumiGard, Fisher and Paykel Healthcare) with standard measures and its impact on the quality of recovery of surgical patients. Method: A single‐centre, triple‐blind, feasibility, randomized controlled trial (RCT) of adults scheduled for planned laparoscopic colorectal surgery. The primary outcome was recruitment. Secondary outcomes included feasibility of blinding, acceptability to patients and suitability of objective measures: patient‐reported quality of recovery using a validated questionnaire (QoR‐40), patient pain scores and semi‐continuous core temperature measurements. Results: Thirty‐nine participants were randomized to either the WHCO2 group ( n  = 19) or standard care alone ( n  = 20). Recruitment to the study was successful and acceptable to patients. Blinding of the surgeons, patients and assessors was effective. Response rates to QoR‐40 were high but ceiling effects were observed, indicating that the tool was unsuitable in this population. Fewer patients in the WHCO2 group reported postoperative nausea and vomiting (PONV) at days 1 (53% vs. 65%) and 3 (37% vs. 60%). The median hospital length of stay was 5.5 days in the standard care group and 4 days in the WHCO2 group. Conclusion: A study of WHCO2 for insufflation in laparoscopic colorectal surgery would be highly acceptable to both patients and researchers. Potential reductions in PONV and hospital length of stay in patients treated with WHCO2 merit further investigation. The design of the full‐scale RCT will benefit from this feasibility study.